Influence of Gamification (Shoppertainment) and Hedonism Value on TikTok Purchasing Decisions: Islamic Economic Perspective - Dinar Ekamanda; Maryam Bte Badrul Munir (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines at how gamification and hedonism value influence product purchasing decisions using the TikTok app, with a focus on Generation Z in Gresik, East Java. The study used quantitative methods and a correlational research design, with a questionnaire distributed to Muslim Generation Z individuals aged 18-28 who were selected through purposive sampling. The data were analyzed with linear regression. The results show that while hedonism value influences purchasing decisions, gamification does not. Gamification and hedonism value both influence product purchasing decisions.